2017
DOI: 10.1111/jfpe.12585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low temperature cooking methods and holding times on selected quality attributes of cooked pork longissimus dorsi

Abstract: This article studied the effects of different cooking methods (water bath, steam, and microwave environments) and holding times ranging from 0 to 9 min on selected quality attributes including cooking loss, Warner‐Bratzler shear force, and water‐holding capacity of cooked pork loin meats. Results indicated that increasing holding time caused the shear force value to increase, then decrease, and then increase again. The minimum shear force value for steam and microwave cooking environments at 75 °C was found at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The value of cooking loss at 100 °C for 65 min was approximately two‐fold higher than at 100 °C for 5 min. Li et al 27 . also reported a similar phenomenon using the same cooking temperature (75 °C) but a different holding time (ranging from 0 to 9 min) on selected quality attributes of cooked pork longissimus dorsi.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The value of cooking loss at 100 °C for 65 min was approximately two‐fold higher than at 100 °C for 5 min. Li et al 27 . also reported a similar phenomenon using the same cooking temperature (75 °C) but a different holding time (ranging from 0 to 9 min) on selected quality attributes of cooked pork longissimus dorsi.…”
Section: Resultsmentioning
confidence: 71%
“…The water holding capacity of braised chicken declined after heat treatment probably as a result of protein oxidation. 27,28 Sobral et al 17 reviewed the heat cooking condition effects on meat protein oxidation and found that the oxidized proteins were correlated with water loss after thermal processing. Meanwhile, the thermal treatment of meat products produced a large number of carbonyls and promoted the Maillard reaction and protein oxidation product formation, which further increased the water loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of three low-temperature cooking methods, i.e. water bath, microwave, and steam on meat tenderness as well as several other quality parameters of pork, was investigated at various times of heat treatment (Li and Sun 2017). The best tenderness values were obtained when the pork samples were cooked with steam for 5 min or microwaved for 7 min.…”
Section: Sensory and Microbiological Analysismentioning
confidence: 99%
“…product Poland (Wojdalski, Drózdz, Grochowicz, Magryś, & Ekielski, 2013) ᵇtHSCW = tonne of hot standard carcass weight Sourced from (Ziara, 2015) geometrical center of the products. This could lead to overheating of the surfaces while waiting for the interior to reach the required temperature (Li, Sun, Han, & Yu, 2017). The choice of appropriate cooking techniques relies on the type of meat, the amount of connective tissue, size and shape of the meat.…”
Section: Importance Of Meat Cookingmentioning
confidence: 99%